Development of optimisation techniques for ultrasonic equipment for the generation of stable oil-in-water emulsion - Lok, Matthew Sze Tsun (2018)
Emulsion is a thermodynamically stable compound consisting of an immiscible mixture of oil and water. Emulsion droplets can be formed through various methods, such as high pressure homogenisation, microfluidiser, ultrasonication, etc. Among all the techniques stated, ultrasonically formed emulsion droplets possess high potential in the nanotechnology field due to its ability to form small emulsion droplet in the size ranges from 100 – 300 nm. Even though there has been extensive research on the formation of various emulsion droplets using ultrasonic technique, there is still lacking of information regarding appropriate optimisation process on the formation of ultrasonically formed emulsion droplets. The aim of this research was to evaluate the characteristics of the ultrasonic equipment, and the factors that may affect the formation of stable oil-in-water emulsion droplets. To achieve that, this work was separated into two distinctive parts. The first part addressed the performance of the ultrasonic equipment via a series of characterisation techniques to determine the actual power output, sonochemical performance through the production of •OH radicals and followed by performing simulation to determine the acoustic pressure fields under different operating conditions. The second part of the research was focused on the optimisation of the formation of emulsion using the information gathered from the characterisation techniques, followed by performing Response Surface Methodology (RSM) to obtain the optimum conditions to form stable emulsion droplets with low polydispersity. Through the results of this work, it could be seen that the position of the ultrasonic source and the dimensions of the vessels used, as well as the distance from the oil-water interface, played an important role in affecting the overall ultrasonic performance of the system. Results showed that placing the ultrasonic horn slightly above the oil-water interface have resulted in the production of higher acoustic pressure. Using an optimal setup of the ultrasonic system, the oil-in-water emulsion formed, in the presence of a suitable amount of surfactant combinations, could be optimised via RSM, to form emulsion droplets of ca. 151 nm, with polydispersity index of 0.18, hence proving that this was a viable method for future optimisation work to obtain desired emulsion parameters required for various applications.